LOVE WAVE SUPPRESSION WITHOUT PRIOR STRUCTURAL INFORMATION - van Zanen L.F.; Wapenaar C.P.A.; Drijkoningen G.G.; Fokkema J.T. (My University, 2003)
Love waves are one of the major contributors of noise in SH -wave reflection data. Suppressing them can be difficult, most importantly because their group velocity is almost equal to the shear wave velocity. By using the Betti-Rayleigh reciprocity theorem for elastic media, modified for SH waves only, we derive an integral equation of the second kind for an ideal wavefield that does not contain the Love waves. No structural subsurface model is needed for solving this integral equation. The equation can be solved numerically, for example by a direct matrix inversion. The method is tested on several synthetic data sets, modelled with the finite difference method. We illustrate both the laterally invariant and the laterally varying situation with examples. Finally, we test the sensitivity of the suppression method, and observe that it is relatively the most sensitive to errors in the phase of the source wavelet.
Keywords: LOVE WAVES; RECIPROCITY; SH WAVES